POTRET PERKAWINAN SUMBANG MASYARAKAT DESA RAMBAH HILIR TENGAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Idrika, Rahmi; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The majority of the people in Rambah Hilir Tengah Village are Malay people, there are two systems namely Ideal Marriage and Contribution Marriage where the marriage procedure is not just done, because they have customs. Moreover, both parties live on the Malay Earth they must know each other about their the origin, family, lineage, and ethnicity. After asking all that, there are irregularities, for example the couple is come from one tribe or also called as a fellow, they want to get married as well, whether or not they have to leave the tribe, and will get a fine in the form of two goats to be given to Datuk Pucuk, Ninik Mamak or Traditional Datuk and Village Apparatus. As the purpose of giving the two goats is to ensure that the nephew of Ninik Mamak Si A has come out of his tribe and entered into the tribe of his father or a tribe that is Seven, Not only that couples who marry one tribe also get sanctions in the form of Customary Fines Karma sanctions, and getting scorn from the community and the couple is wasted throughout Adat. Then the factor of the marriage of one tribe is a lack of knowledge of indigenous issues, Religion that does not prohibit, Lack of knowledge about adat from parents, matchmaking is also included in the factor encouraging someone to marry one tribe. This study uses qualitative research using social deviation theory. Keywords: Marriage, tribe, Costom, Sanction